E-Gov on the Sicantik Application at the Investment and One-Door Integrated Services Service (DPM-PTSP) Gorontalo Regency - Harun, Sintia R.; Akbar, Muh. Firyal; Gintulangi, Sri Lestari; Botutihe, Nuzlan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the implementation of e-government through the use of the SiCantik (Smart Integrated Licensing Service) application at the Gorontalo Regency Investment and One-Stop Integrated Service Office (DPM-PTSP), and to identify various technical and non-technical obstacles that hinder the effectiveness of licensing services. The research method used was a qualitative descriptive method with a case study approach. Data were obtained through field observations, interviews, and documentation of DPM-PTSP employees and service users. The results indicate that the implementation of the SiCantik application has not been optimally implemented. This is due to frequent system maintenance without an effective emergency mitigation mechanism, a high dependence on internet network stability, and limited technical competence of staff in handling system issues. These conditions have implications for the licensing service process and reduced the efficiency and effectiveness of organizational performance. However, the transition from a manual system to an application-based system has had a positive impact on improving the quality of public services. This is evidenced by an 80% increase in permit applications from the first to the fourth quarter. Furthermore, network infrastructure management by the Gorontalo Regency Communication and Informatics Agency (KOMINFO) is considered optimal, supporting the continuity of service operations. Based on the research findings, it is recommended that the SiCantik application center administrator provide a more effective emergency mitigation mechanism, improve coordination between the DPM-PTSP (Directorate General of Public Service) and KOMINFO in system maintenance, and strengthen the technical competence of civil servants through ongoing training. These steps are expected to improve system reliability, streamline service processes, and achieve a more optimal implementation of e-Government within the local government.